2017
DOI: 10.1039/c7ta06204d
|View full text |Cite
|
Sign up to set email alerts
|

General promoting effect of polydopamine on supported noble metal catalysts

Abstract: A joint experimental–theoretical study has been conducted to investigate the role of polydopamine as an interface facilitator for supported noble metal catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
0
30
0
1
Order By: Relevance
“…It is widely accepted that capping molecules adsorb to the metal surface to change its surface energy . Li et al . indicated that the reaction rate constant is related to the intitial adsorption of 4‐NP on the catalyst of noble mental.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is widely accepted that capping molecules adsorb to the metal surface to change its surface energy . Li et al . indicated that the reaction rate constant is related to the intitial adsorption of 4‐NP on the catalyst of noble mental.…”
Section: Resultsmentioning
confidence: 99%
“…It is conjectured that π‐π or p‐π strong interaction between the giant π bonds of rGO nanosheet and benzene ring of 4‐NP . Besides, dextran with multiply hydroxyl groups on Pt NPs can withdraw electrons of Pt‐NPs to reach the optimal adsorption energy of reactant ,,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein, MoS 2 nanosheets have been shown to be promising candidate components for various fields, such as the detection of water-soluble substances, humidity, and gas species. [22][23][24][25][26] MBAMS was prepared via MoS 2 exfoliation processes and subsequent chemical functionalization process with 4-MBA for realizing the reactivity and selectivity toward the target substance. Here, 4-MBA, a small ligand molecule with a thiol and a carboxyl group, was used to modify the surface of MoS 2 nanosheets.…”
mentioning
confidence: 99%